International perspectives on the supply of informal venture capital - Harrison, Richard T.; Mason, Colin M. (Journal of Business Venturing, 1992)
Despite major changes in the number and range of sources of finance for new and small ventures in the United Kingdom in recent years, there continues to be a shortage of risk capital for ventures actively seeking external equity finance. In the United States the informal venture capital market plays a major role in filling this equity gap, particularly in the early stages of venture development. However, there is little comparable information on the size of the informal venture capital pool in the United Kingdom or other European economies, despite recent recognition that the apparent underdevelopment of this market in the U.K. represents a major barrier to the development and growth of new ventures. This paper, therefore, presents the first analysis of the informal venture capital market in the U.K. and compares the characteristics and attitudes of U.K. informal investors with those in the U.S. The data reported in this paper have been obtained from a combination of postal survey and snowball sample techniques that generated useable information from 86 informal investors. Informal investors are playing an important role in venture financing in the U.K. in three ways: they make small scale investments in new and early stage ventures, where the equity gap is most significant; they are more permissive in their financing decisions than the formal venture capital industry in terms of having lower rejection rates, longer exit horizons, and lower target rates of return; and they invest locally and can thereby close the regional equity gap arising from the overconcentration of venture capital investment in the core South-East region in the U.K. In terms of demographics, U.K. informal investors share many of the characteristics of North American informal investors: they are predominantly male, with an entrepreneurial background, financially well-off without being super-rich, and identify investment opportunities from friends and business associates. There are a number of key differences, that may be attributable to differences in contextual factors such as personal tax regimes, regulatory environments, wealth distribution, and the structure of the formal venture capital and IPO markets. For example, U.K. informal investors are significantly older than those in the U.S. reflecting the influence of higher U.K. tax rates on the rate of capital and wealth accumulation. More generally, in comparison to U.S. investors, U.K. informal investors: have more investment opportunities brought to their attention; seriously consider more proposals but invest in no more opportunities; operate independently with syndication and joint investment relatively uncommon, reducing the average total investment per financing round available to ventures; fail to identify entrepreneurs themselves as a primary source of information on investment opportunities; have higher rate of return and capital gains expectations; are slightly less patient investors; and are rather less satisfied with the overall performance of their informal investment portfolios, reflecting intercountry and intertemporal variations in investment climate and conditions. It appears, therefore, that the general inefficiency of the informal capital market identified by Wetzel (1987) (which reflects the invisibility of informal investors, the fragmented nature of the market, and the imperfect channels of communication between investor and entrepreneur) is compounded in the U.K. case. The extent to which this reflects contextual differences on the one hand or simply a slower developmental process in the U.K. will only be common methodological basis. Based on the evidence presented in this paper, however, a key conclusion is that the information networks available to U.K. informal investors are less effective than those in North America, and in particular appear to contain lower quality information and a higher degree of redundant information. Specific forms of intervention in the market by, for example, stimulating the flow of information through the promotion of informal investment networking and brokerage services along the lines of U.S. and Canadian examples such as VCN and COIN therefore appear defensible.